Strategi Pendidik di SLB Negeri Sumut dalam Membangun Motivasi Belajar Siswa Tunagrahita - Nurmayani Nurmayani; Bonika Alprianta Sari Hulu; Fifi Amelia Sitinjak; Friclia Dhea Lova Siagian (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study analyzes the strategies used by educators to improve learning motivation of mentally retarded students at SLB Negeri North Sumatra. The method used is descriptive qualitative, with data collection through observation, semi-structured interviews, and documentation. The subjects of the study consisted of mentally retarded class teachers and seven students with varying levels of difficulty. The results showed that students' learning motivation varied, with some students showing enthusiasm for fun and relevant activities. The five main strategies applied by teachers include: (1) individual and contextual learning strategies with an emphasis on the learning by doing method, (2) the use of varied learning media such as visual media, flashcards, learning videos, and interactive applications, (3) giving rewards in the form of verbal praise and small prizes and proportional educational punishments, (4) creating a safe, comfortable, and supportive learning environment with positive communication, and (5) active cooperation with parents through communication. The main supporting factors are teachers, a school environment, and good relationships with parents, while inhibiting factors include low parental awareness and students' socio-economic conditions. The success of the strategy can be seen from the increase in more active student behavior. This study concludes that the learning motivation of mentally retarded students can be increased through an adaptive approach that involves all parties.